Determinan Pencegahan Fraud dalam Pengelolaan Dana Desa - Adhivinna, Vidya Vitta; Cinde Sanjiwani, Agni; Umam, M. Sulkhanul (Universitas PGRI Yogyakarta, 2025)
This study aims to examine the impact of personnel competence, internal control systems, whistleblowing, and organizational culture on the prevention of fraud in the management of village funds in 13 villages in Kapanewon Playen, Gunungkidul Regency. The sample was selected using a non-probability purposive sampling method, involving 92 respondents, including village heads, secretaries, treasurers, planners, irrigation officers, finance staff, planning staff, and heads of village consultative bodies in the 13 villages of Kapanewon Playen. Data were collected through questionnaires distributed to all respondents. Data analysis was conducted using multiple linear regression with IBM SPSS 25 software. The study's results indicate that personnel competence and internal control systems do not affect fraud prevention in the management of village funds, while the whistleblowing system and organizational culture have a positive impact on fraud prevention in the management of village funds. These findings are expected to be a consideration in efforts to enhance fraud prevention in the management of village funds.